Cost assessment and benefits of using RFID in reverse logistics of waste electrical & Electronic equipment (WEEE) - De Araujo, Marcus Vinicius F. [UNESP]; De Oliveira, Uanderson R. [UNESP]; Marins, Fernando A. S. [UNESP]; Muniz, Jorge [UNESP] (Elsevier, 2015)
The Radio Frequency Identification (RFID) has been increasingly used in order to leverage aspects related to products and services such as: safety, convenience, authentication, process efficiency. As its name suggests, the basis of this technology is to use the instrument of communication by radio frequency data transmission. Application of such technology in cases of theft prevention products, access control of people, payments, product management, process management and monitoring/ tracking/ supply chain integration, are evidence of their increasing economic viability, especially considering the continuous and progressive increase in the use of scale. Considering the growing global concern about a more efficient management of natural resources and their recycling, this paper presents cost assessment and benefits of using RFID in Reverse Logistics of electronics waste (e-waste), specifically in Brazil.
Keywords: E-waste; Reverse logistics; RFID; Solid waste